Peningkatan Keterampilan Berpikir Kreatif Melalui Penerapan Model Pembelajaran Mind Mapping - Istiningsih, Anif; Mawardi, Mawardi; Intan Permata, Herlina Kasih (Universitas Muhammadiyah Magelang, 2019)
This study was aims to explain the efforts to improve creative thinking skills of fifth grade students of SDN Tingkir Lor 02 using the Mind Mapping learning model in the 2018/2019 academic year. This type of research is Classroom Action Research. The research subjects were fifth grade students of SDN Tingkir Lor 02, 2018/2019 school year, totaling 31 students. Data collection techniques in this study used observation. The data analysis technique used is quantitative descriptive and qualitative descriptive analysis techniques. The results showed that the mind mapping learning model could improve the creative thinking skills of fifth grade students of SDN Tingkir Lor 02. After the study was held, the results obtained in the learning cycle I were from 31 students, 9 students (29.03%) received the title